“I Grew Up Amidst Alcohol and Drugs:” a Qualitative Study on the Lived Experiences of Parental Substance Use Among Adults Who Developed Substance Use Disorders Themselves - Meulewaeter, Florien; De Schauwer, Elisabeth; De Pauw, Sarah S. W.; Vanderplasschen, Wouter (Frontiers in Psychiatry, 2022)
Experiencing parental substance use (PSU) has been associated with a heightened risk of developing substance use disorders (SUDs) in offspring. The primary goal of this study was to explore perspectives of adult children with lived experience of PSU who also developed SUDs themselves through first-hand experience. This study was conducted in Flanders (Belgium). A qualitative exploratory research design was applied. Seventeen semi-structured interviews were conducted with adult children of parents with SUDs (range: 29-48 years) who themselves had developed SUDs. All interviews were audio-taped and transcribed verbatim. Three overarching themes emerged through thematic analysis: 1) loneliness and neglect in childhood; 2) stigma and the self; and 3) the role of social connection in substance use and recovery. The narratives highlighted the central role of feelings of loneliness, isolation and belonging among children of parents with SUDs in childhood and adulthood. Increasing public awareness on the impact of PSU on children and accessible support is needed to overcome stigma and remove barriers to social inclusion for children of parents with SUDs. Findings may prove valuable in informing policy, program and treatment development. aimed at breaking maladaptive intergenerational cycles.